2016
DOI: 10.1016/j.fishres.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic structure in the saddled sea bream (Oblada melanura [Linnaeus, 1758]) suggests multi-scaled patterns of connectivity between protected and unprotected areas in the Western Mediterranean Sea

Abstract: Spatial genetic structure in the saddled sea bream (Oblada melanura [Linnaeus, 1758] a b s t r a c tMarine protected areas (MPAs) and networks of MPAs are advocated worldwide for the achievement of marine conservation objectives. Although the knowledge about population connectivity is considered fundamental for the optimal design of MPAs and networks, the amount of information available for the Mediterranean Sea is currently scarce. We investigated the genetic structure of the saddled sea bream (Oblada melanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Samples collected outside of the Lundy NTZ reported similar levels of genetic diversity to the Lundy NTZ sample, which is also compatible with a lack of isolation for the Lundy NTZ. Calò et al (2016) reported similar levels of genetic diversity for protected and unprotected areas in the saddled sea bream (Oblada melanura). This pattern differs from the study including two MPAs in the western Mediterranean by Pérez-Ruzafa et al (2006) that reported higher values of total and standardised allelic richness in protected populations of Diplodus sargus than in unprotected ones.…”
Section: Discussionmentioning
confidence: 87%
“…Samples collected outside of the Lundy NTZ reported similar levels of genetic diversity to the Lundy NTZ sample, which is also compatible with a lack of isolation for the Lundy NTZ. Calò et al (2016) reported similar levels of genetic diversity for protected and unprotected areas in the saddled sea bream (Oblada melanura). This pattern differs from the study including two MPAs in the western Mediterranean by Pérez-Ruzafa et al (2006) that reported higher values of total and standardised allelic richness in protected populations of Diplodus sargus than in unprotected ones.…”
Section: Discussionmentioning
confidence: 87%
“…In the case of marine fishes, previous studies have highlighted the importance of these various spatial scales. In the Mediterranean, some studies highlighted the importance of the dispersal capacities of fishes at the egg, larval, juvenile and recruit stages 5 7 . Regarding habitat characteristics, complex habitats formed by macrophytes have been proved to host more abundant and/or more diversified communities compared to simpler habitats 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Calo et al . (2016) also reported similar levels of genetic diversity for protected and unprotected areas in the saddled sea bream ( Oblada melanura ). While we do not have samples from before the commencement of commercial harvesting or during the initial stages of exploitation when loss of diversity may be most pronounced (Ryman et al ., 1995) and thus cannot rule out the possibility that some genetic variation has been lost due to fishing, the results indicate that high levels of genetic variation are maintained within the species which is fundamental for maintaining sustainable yields and adaptability of populations (Kenchington et al ., 2003).…”
Section: Discussionmentioning
confidence: 77%